Students’ perceptions of teachers’ use of first language in the esp classrooms: a case study at university of languages and international studies = quan điểm của sinh viên về việc sử dụng tiếng việt của giảng viên dạy tiếng anh chuyên ngành: điển cứu tại Trường đại học Ngoại ngữ, đại học Quốc gia Hà nội - Đặng, Phương Thảo (2021)
Vietnam has been making its way into the global economy, and on that account, the learning of English has been of paramount importance, especially English for Specific Purposes. However, it remains controversial whether mother tongue should be used in ESP teaching due to existence of debatable theories on the presence of L1 in L2 classrooms. This study investigated the practice of using Vietnamese by teachers at University of Languages and International Studies, as well as the perceptions of ESP students towards employing Vietnamese in ESP classrooms. Data was collected by means of questionnaires and semi-structured interviews with 65 English-International Economics undergraduates. The findings revealed that ESP practitioners often used Vietnamese in specific situations such as explaining technical terms, establishing rapport with students and addressing administrative issues. The results also suggested that ESP learners regarded mother tongue as a doublededged tool in ESP classrooms. In addition, recommendations in terms of pedagogical methodology and improvements were also proposed for further related studies.